(untitled) (Journal of the Sylhet Agricultural University, 2025)
Climate change has gradually affected forest ecosystems globally and it has also happened at the adjacent areas of Ratargul Swamp Forest at Gowainghat Upazila in Bangladesh. This study documented climatic alterations and community-initiated adaption measures on climate change. Ratargul, the sole freshwater swamp forest in Bangladesh, is an essential life line for local ecology and also livelihoods of the local community. The study was accomplished through a survey of 65 randomly selected local people and employed meteorological data and people perception in respect of changing of climatic parameters. Results indicated that the demographic profile of the most people were middle-aged (47.7%), about 42% had medium income and 31% had only primary-level education. The majority of individuals near the forest work in the business sector (40%) followed by agriculture (29%). Meteorological data showed a steady rise in maximum and minimum temperatures over time, where increment rate per year of maximum and minimum temperatures were 0.0194°C and 0.0832°C, respectively. An increase in rainfall at the rate of 54.12 mm was also estimated. People perception and meteorological data together draw a scenario of climate change and the livelihood of the inhabitants living near the forest area. Around 49.2% respondents agreed that Akashmoni (Acacia auriculiformis) plantation increased at Ratargul Swamp Forest while some tree species like Bot (Ficus benghalensis) decreased in the forest according to 24.6% of the respondents but overall tree species decreased due to increasing population and its major influence was in the reduction of tree species in forest reported by 46.20% respondents. Rice (80%) is the principal crop; however, cropping practices have changed due to some climate induced factor. Increase in insect and pest attack (40%) and flooding (38.50%) were the major reasons of changes in cropping in the study area. People have already adopted several adaptation measures like new tree introduction (84.60%) and vegetable crop cultivation (36.90%) and these were some of the adoptive strategies. Major problems faced by the community people were poverty according to 73.8% of the residents, with 69.2% reporting insufficient transportation. Around 86.2% of the respondents reported that poverty can be tackled effectively by increasing employment opportunities in eco-tourism which is again can be possible by increasing transportation facility (83%) in the study area. Finding of this study can be used for policy making, environmental conservation and proper strategies to manage the climate change. J. Sylhet Agril. Univ. 11(1): 83-96, 2024